2019
DOI: 10.1002/smtd.201900026
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Graphene‐Based Liquid Cell Electron Microscopy: Working Principles, Opportunities, and Challenges

Abstract: Imaging materials and biological structures in a liquid environment pose a significant challenge for conventional transmission electron microscopy (TEM) due to stringent requirement of ultrahigh vacuum design in the microscope column. The most recent liquid‐cell TEM technique, graphene liquid‐cell (GLC) microscopy, employs only layers of graphene to encapsulate liquid specimens. Recent efforts with GLC–TEM have demonstrated superior imaging resolution of beam‐sensitive specimens. Herein, the parameters that af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 139 publications
(287 reference statements)
0
44
0
Order By: Relevance
“…In order to improve the thermal stability of the cathodes and simultaneously maintain the electrochemical properties, the surface coating of cathodes should meet a number of requirements: 1) it should be impermeable to the oxygen gas but allow for the Li‐ion transfer, 2) have high electronic conductivity, 3) remain stable in contact with the electrolyte, and 4) be scalable and cost effective . In this regard, atomically thin graphene and its derivatives such as reduced graphene oxide (rGO) appear to be good candidates since it has been shown that graphene and rGO are impermeable to liquids and gases specially oxygen . Reduced graphene‐oxide has shown a great potential in the gas barrier applications .…”
Section: Introductionmentioning
confidence: 64%
“…In order to improve the thermal stability of the cathodes and simultaneously maintain the electrochemical properties, the surface coating of cathodes should meet a number of requirements: 1) it should be impermeable to the oxygen gas but allow for the Li‐ion transfer, 2) have high electronic conductivity, 3) remain stable in contact with the electrolyte, and 4) be scalable and cost effective . In this regard, atomically thin graphene and its derivatives such as reduced graphene oxide (rGO) appear to be good candidates since it has been shown that graphene and rGO are impermeable to liquids and gases specially oxygen . Reduced graphene‐oxide has shown a great potential in the gas barrier applications .…”
Section: Introductionmentioning
confidence: 64%
“…Also, the specimen holder preparation usually demands efforts to deposit materials onto electrodes, if required. The graphene liquid cell method, for the moment, is less feasible, but it yields superior spatial resolution and many new imaging possibilities . Kühne et al provide an effective example of combining reliable electrode designs with the graphene liquid cell.…”
Section: Energy Storagementioning
confidence: 99%
“…SiO 2 [4,5]. There are many suggestions of practical usage of the bubbles inside van der Waals heterostructures, for example, the graphene liquid cell microscopy [6], controlled room-temperature photoluminescence emitters [7], etc.…”
mentioning
confidence: 99%